Unlocking Insights from 10 Years of Digital Forensic and Forensic Anthropology Population Data in Law Journals - Haniah Kurniawati, Dilla; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
In this data article, we present the results of a comprehensive search on Lens.org, aimed at gathering research articles related to "Digital Forensic" and "Forensic Anthropology Population Data" with a focus on the field of law. Our goal was to quantify the available literature and facilitate future research in the intersection of digital forensic and forensic anthropology population data. Our methodology involved keyword-based searches, followed by filtering for "Journal Articles," a 10-year publication range (2012-2022), and a subject matter of "Law." The findings reveal a total of 69 relevant journal articles, offering a valuable resource for researchers and scholars interested in the nuances of digital forensic investigations in the context of population data and legal aspects. This dataset serves as a springboard for further insights, making it accessible for a global community of scientists exploring the dynamic landscape of digital forensics and law.Highlights : Data gathering: Comprehensive search on Lens.org for digital forensic and forensic anthropology data in law journals. Filtering criteria: Document type, publication range, and subject matter to refine results. Valuable resource: 69 journal articles collected, enabling future research in this intersection. Keywords: Digital Forensic, Forensic Anthropology, Law Journals, Data Analysis, Research Insights.